2006
DOI: 10.1037/0096-3445.135.2.152
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the near and distant future.

Abstract: Four studies investigated individuals' confidence in predicting near future and distant future outcomes. Study 1 found that participants were more confident in theory-based predictions of psychological experiments when these experiments were expected to take place in the more distant future. Studies 2-4 examined participants' confidence in predicting their performance on near and distant future tests. These studies found that in predicting their more distant future performance, participants disregarded the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(95 citation statements)
references
References 34 publications
3
87
0
3
Order By: Relevance
“…We note, however, that the association of trait attributions with social distance is speculative in our study, as we did not measure social distance directly. Nevertheless, the link between trait attributions and distance is empirically well supported by multiple studies showing that humans tend to make more trait attributions for people who are more psychologically, socially, and physically remote (Henderson, Fujita, Trope, & Liberman, 2006;Nussbaum et al, 2003;Nussbaum, Liberman, & Trope, 2006;Rim, Uleman, & Trope, 2009).…”
Section: Discussionmentioning
confidence: 95%
“…We note, however, that the association of trait attributions with social distance is speculative in our study, as we did not measure social distance directly. Nevertheless, the link between trait attributions and distance is empirically well supported by multiple studies showing that humans tend to make more trait attributions for people who are more psychologically, socially, and physically remote (Henderson, Fujita, Trope, & Liberman, 2006;Nussbaum et al, 2003;Nussbaum, Liberman, & Trope, 2006;Rim, Uleman, & Trope, 2009).…”
Section: Discussionmentioning
confidence: 95%
“…For example, when people are asked to make predictions about their performance in an upcoming quiz, these predictions were more influenced by their perceived competence (an abstract, high-level consideration) than by specific task characteristics of the quiz (concrete, low-level considerations) when the quiz was in the far future. The opposite was true when the quiz was planned in the near future (Nussbaum, Trope, & Liberman, 2001; see also Nussbaum, Liberman, & Trope, 2006).…”
Section: Running Head: Antecedents Of Justice Expectationsmentioning
confidence: 99%
“…By passing through the selection procedure and through a process of experiential learning (Kolb, 1984), applicants learn about the procedure and about the dominant role that tests play in determining one"s outcome. On the basis of this experience, applicants will adjust their notion of belief in tests, incorporating more concrete and contextualized details (Nussbaum, Liberman, & Trope, 2006). Based on CLT, it can then be suggested that this more concrete belief will more strongly influence predictions for the near future (i.e., forthcoming selection procedure) than the initial abstract belief in test.…”
Section: Running Head: Antecedents Of Justice Expectationsmentioning
confidence: 99%
“…Similarly, temporal distance leads people to focus on more abstract, higherorder concepts in future predictions than on more concrete, lower-order concepts (e.g., Fujita, Trope, Liberman, & Levin-Sagi, 2006;Nussbaum, Liberman, & Trope, 2006;Trope & Liberman, 2003). Walton and Banaji (2004) have further shown that abstract linguistic forms invoke characterological or essential features, whereas more concrete linguistic forms invoke features that are likely to fluctuate over time and across situations (cf.…”
Section: Linguistic Forms and The Subjective Distance From The Past mentioning
confidence: 99%